89.0k views
3 votes
Simplify (3/4 + 4/5i)-(1/2 - 3/10i)

User Muirik
by
5.0k points

1 Answer

7 votes

For this case we must simplify the following expression:


(\frac {3} {4} + \frac {4} {5} i) - (\frac {1} {2} - \frac {3} {10} i) =

By law of multiplication signs we have to:


- * + = -\\- * - = +\\\frac {3} {4} + \frac {4} {5} i- \frac {1} {2} + \frac {3} {10} i =

We add similar terms:


\frac {3} {4} - \frac {1} {2} + \frac {4} {5} i + \frac {3} {10} i =\\\frac {3 * 2-4 * 1} {4 * 2} + \frac {4 * 10 + 5 * 3} {10 * 5} i =\\\frac {2} {8} + \frac {55} {50} i =

We simplify:


(1)/(4)+(11)/(10)i

Answer:


(1)/(4)+(11)/(10)i

User Silvernightstar
by
5.3k points